Application Of A Combination Of Deep Breathing Relaxation Techniques And Warm Compresses To Reduce Pain Dyspepsia Patients at H Abdul Manap Hospital - Khopipah, Nahdiah; Martawinarti, Rts Netisa (Jurnal Keperawatan Universitas Jambi, 2024)
Background: Dyspepsia is a symptom that is often found in society which is characterized by pain and discomfort in the upper part or solar plexus and has a negative impact on the sufferer's productivity. One of the non-pharmacological therapies applied to reduce chest/heartburn pain in dyspepsia patients is a combination of deep breathing relaxation techniques and warm compresses. Objective: This research was conducted to determine the effect of a combination of deep breathing relaxation techniques and warm compresses on pain intensity in dyspepsia patients. Method: Using a case report design, in dyspepsia patients who experienced mild-moderate chest/heartburn pain, with one intervention patient and one control patient, which was measured using the Numeric Rating Scale. This research was carried out for 3 days, treatment 2 times a day for 15-30 minutes. Results: Results were obtained in intervention patients whose pain scale was initially 6 moderate, decreasing to 0 no pain, while in control patients whose pain scale was initially 7 severe, the pain scale was 1 no pain. Conclusion: The application of a combination of deep breathing relaxation techniques and warm compresses shows changes and obtains optimal and well-documented results. It is hoped that future researchers can develop case report results related to reducing pain intensity in dyspeptic heartburn patients.